Analisis Litologi Bawah Permukaan Kawasan Longsor di Jalan Lintas Barat KM-25 dengan Resistivitas 2-Dimensi - Amsir Amsir; Meikel Suryanta Sembiring; Zakia Masrurah; Dian Darisma; Tomi Afrizal (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study aims to analyse the subsurface lithology in the landslide-prone area at KM-25 West Cross Road using a 2-dimensional resistivity method with a dipole-dipole configuration on two measurement tracks. The inversion results reveal significant lithological heterogeneity, with a low resistivity zone (<50 Ωm) at a depth of 5-20 metres, interpreted as a water-saturated clay layer or weathered material. The physical properties of this layer contribute to increased pore pressure, potentially forming a slip plane. The transition zone between the saturated clay layer and hard rock with high resistivity (>100 Ωm) is identified as a geomechanically weak zone prone to ground movement, primarily when saturation occurs due to heavy rainfall. The resistivity cross-section of the second pass shows similar features, with a thicker and wider zone of very low resistivity (<30 Ωm), indicating the presence of soft clays or unconsolidated fill. These results emphasise the importance of early detection of subsurface resistivity contrasts as indicators of landslide potential. This research provides an essential contribution to disaster mitigation efforts and can serve as a basis for spatial planning and infrastructure design to enhance resilience against geological hazards.